The Influence of the Shopee Live Feature, Shopee Tanam Gamification, and Personalized Product Recommendation on Impulse Buying among Shopee Consumers in Indonesia. - Gabriela Amanda Salim; Dave kwok; Isna Asdiani Nasution; Melisa Zuriani Hasibuan (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Purpose – This study aims to analyze the influence of the Shopee Live Feature, Gamification (Shopee Tanam), and Personalized Product Recommendation on Impulse Buying behavior among Shopee consumers in Indonesia. The research focuses on young consumers as the dominant group within the digital e-commerce ecosystem. Novelty – The novelty of this study lies in the simultaneous examination of three interactive digital features—Shopee Live Feature, Gamification (Shopee Tanam), and Personalized Product Recommendation—which have rarely been investigated in an integrated manner within the context of Indonesian e-commerce. This study provides empirical insights into how the combination of digital interactivity and personalization influences impulsive purchasing behavior. Method – This study employs a quantitative approach using an online survey with 300 Shopee users aged 30 years or younger. All research instruments satisfied reliability tests and classical assumption requirements. Findings – The results indicate that the Shopee Live Feature (β = 0.431; Sig. = 0.000), Gamification (Shopee Tanam) (β = 0.332; Sig. = 0.000), and Personalized Product Recommendation (β = 0.296; Sig. = 0.000) have a positive and significant effect on Impulse Buying. Simultaneously, the three independent variables significantly influence Impulse Buying (F = 51.514; Sig. = 0.000), with an R² of 0.343, indicating that 34.3% of the variation in Impulse Buying behavior is explained by the research model. Limitations and Implications – This study is limited to young Shopee users in Indonesia; therefore, the findings cannot yet be generalized to other e-commerce platforms. The results have practical implications for e-commerce industry practitioners, suggesting that they optimize marketing strategies based on interactivity, gamification, and personalization to effectively stimulate consumers’ impulsive purchasing behavior